Gambaran Perilaku Mengenai Nutrisi dan Perubahan Perilaku Masyarakat Mengenai Hidup Sehat Selama Pandemi COVID-19 - Ade Pryta Simaremare (Faculty of Medicine, Universitas Andalas, 2021)
Introduction: COVID-19 is a disease caused by SARS Cov-2. At present, there is no specific antiviral treatment found. The most appropriate action to take is prevention to break the chain of transmission of the virus to other people. These efforts include meeting his daily nutritional needs and changing physical activity because most of his time is spent at home because he is required to do physical / social distancing.Purpose: To get a description of the behavior regarding nutrition and changes in the behavior of the Indonesian people regarding healthy living during the COVID-19 pandemic.Methods: This study used an analytic observational design with a cross sectional method. The samples in this study are all Indonesian people who have social media. Sampling was done using online participatory techniques.Results: The majority of respondents have good knowledge, attitudes, and actions regarding nutrition during the COVID-19 pandemic and pay more attention to nutritional needs and physical activity to increase immunity.Conclusion: The community has an important role in efforts to prevent the transmission of Covid-19.Keywords: COVID-19, immunity, nutrition, physical activity